TBHQ Suppresses Osteoclastic Resorption in Xenogeneic‐Treated Dentin Matrix‐Based Scaffolds. Issue 18 (11th July 2017) - Sun, Jingjing; Li, Jie; Li, Hui; Yang, Hefeng; Chen, Jinlong; Yang, Bo; Huo, Fangjun; Guo, Weihua; Tian, Weidong
Abstract : Extracellularmatrix (ECM)‐based scaffolds are important for their potential therapeutic application. Treated dentin matrix (TDM), a kind of ECM, seeded with allogeneic dental follicle stem cells (TDM/aDFC) provides a suitable inductive microenvironment for tooth root regeneration. Considering the limited sources, xenogeneic TDM (xTDM) is a possible alternative to allogeneic TDM; however, xTDM‐based scaffold presents severe osteolysis and resorption lacunae causing regenerated tooth root failure. Immune response–induced excessive osteoclastogenesis plays a critical role in xenogeneic scaffold osteolysis and resorption. The impact of antioxidant, tert ‐butylhydroquinone ( t BHQ), on xTDM/aDFCs‐induced osteoclastogenesis and osteoclastic resorption in vivo and in vitro are investigated. t BHQ upregulates heme oxygenase‐1 release and downregulates high mobility group box 1 mRNA expression. mRNA expression of other osteoclast‐related genes including nuclear factor‐kappa Bp65, receptor activator of nuclear factor kappa‐B, nuclear factor of activated T‐cells cytoplasmic 1, cathepsin K, and integrin β3, also decreases significantly. Furthermore, t BHQ‐treated xTDM/aDFCs scaffolds implanted into rhesus macaques show reduced osteolysis and osteoclastic resorption by microcomputed tomography and tartrate‐resistant acid phosphatase staining. t BHQ‐induced suppression of xTDM/aDFC‐induced osteoclastogenesis and osteoclastic resorption presents a new strategy for the regeneration of biological tooth root and could be applied to the regeneration of other complex tissues and organs. Abstract : Xenogeneic‐treated dentin matrix (xTDM)‐based scaffolds present severe osteolysis and resorption lacunae causing regenerated tooth root failure. Antioxidant, tert ‐butylhydroquinone ( t BHQ), inhibits xTDM seeded with allogeneic dental follicle cells (xTDM/aDFCs)‐induced osteoclastogenesis and reduces osteolysis and osteoclastic resorption of xTDM/aDFCs scaffolds. The regenerated tooth root constructed of xTDM and aDFCs keep intact and regular in jaws of rhesus macaques under t BHQ treatment.